Involvement of serotonin and eicosanoids in the rat paw oedema response to the essential oil of Pilocarpus spicatus - J. C. R. Silva; V. S. N. Rao (Mediators of Inflammation)
Subplantar injection of Pilocarpus spicatus essential oil (PSEO), induced rat hindpaw oedema in a dose-dependent manner. The time course study revealed that when compared to carrageenan-induced oedema, the oedema response to PSEO was greater at 1 h post-injection, and thereafter remained relatively constant until 5 h post-injection. By 24 h, it was still at almost the 50% level. This effect of PSEO was characterized using several inhibitors of oedema formation. Pretreatment with the H1-receptor antagonist chlorpheniramine did not affect this response, while a significant reduction of paw oedema was achieved with the serotonin antagonist methysergide, but only 1 h and 2 h after injection of PSEO. The oedemagenic activity of PSEO was also suppressed by pretreating the rats with the eicosanoid synthesis inhibitors, phenylbutazone, EP 10161 and dexamethasone. This last drug showed the greatest potency. These findings suggested a probable injury to dermal mast cells and liberation of arachidonate metabolites and eicosanoids at the late phase of oedema induced by PSEO.